Oxidative damage and antioxidant enzyme activities in experimental hypothyroidism - Yilmaz, S; Ozan, S; Benzer, F; Canatan, H (Wiley, 2003)
Free radicals are now well known to damage cellular components. To investigate whether age and thyroid level affect peroxidation speed, we examined the levels of malondialdehyde and antioxidant enzyme activities in different age groups of hypothyroid rats. Hypothyroidism was induced in 30- and 60-day-old Wistar Albino rats by the i.p. administration of propylthiouracil (10 mg kg(-1) body weight) for 15 days. While malondialdehyde levels of 30- or 60-day-old hypothyroid rats were increased in liver, they were decreased in the tissues of the heart and thyroid. While glucose-6-phosphate dehydrogenase activity levels did not change in heart, brain and liver tissues of 30-day-old rats, they increased in brain and heart tissues of 60-day-old experimental groups, but decreased in the liver. Catalase activities decreased in the liver and heart of rats with hypothyroidism, but increased in erythrocytes. In control groups while malondialdehyde levels increased in brain, heart and thymus with regard to age, they decreased in plasma. Glucose-6-phosphate dehydrogenase and catalase activities were not affected by age in tissues of the thymus, thyroid and brain, but they were decreased in the heart tissue. The changes in the levels of lipid peroxidation and antioxidant enzyme activities which were determined in different tissues of hypothyroid rats indicate a cause for functional disorder of these tissues. Moreover, there may be changes depending on age at lipid peroxidation and antioxidant enzyme activity levels. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: hypothyroidism; catalase; glucose-6-phosphate dehydrogenase; malondialdehyde